The Influence of Intrinsic Motivation and Organizational Culture on Organizational Citizenship Behavior (OCB) among Employees of the Regional Secretariat of City XYZ - Eva Nurhalizah; Siti Maryam (International Journal of Business, Economics, and Social Development, 2026)
Improving employee performance in the public sector requires not only formal task completion but also voluntary behaviors that support organizational effectiveness. One important form of such behavior is Organizational Citizenship Behavior (OCB), which reflects employees’ willingness to contribute beyond their formal responsibilities. This study aims to examine the influence of intrinsic motivation and organizational culture on Organizational Citizenship Behavior among employees of the XYZ City Regional Secretariat. The research adopts a quantitative associative approach using a survey method. Data were collected through questionnaires distributed to 120 employees selected using proportionate stratified random sampling from a population of 171 employees. The data were analyzed using statistical techniques with the assistance of SPSS software, including validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing through t-test and F-test. The results indicate that intrinsic motivation has a positive and significant effect on Organizational Citizenship Behavior, suggesting that employees with strong internal motivation are more likely to demonstrate voluntary behaviors that support organizational performance. Organizational culture also shows a positive and significant effect on Organizational Citizenship Behavior, indicating that a supportive and value-driven work environment encourages employees to engage in cooperative and pro-social behaviors. Furthermore, intrinsic motivation and organizational culture simultaneously have a significant influence on Organizational Citizenship Behavior, demonstrating that the combination of strong personal motivation and a positive organizational environment plays an important role in enhancing extra-role behavior among employees. These findings highlight the importance of strengthening both intrinsic motivation and organizational culture to improve employee engagement and organizational effectiveness in the public sector.